A Bibliometric Analysis of Neurofeedback Studies in Cognitive Impairment : Current Trends and Future Directions in Malaysia - Siti Atiyah, Ali; Humaira, Nisar (2023)
Neurofeedback training (NFT) is a brain wave self-training method that has gained attention in recent years, especially as an alternative for neurorehabilitation specifically for people with cognitive impairment (CI). In this short bibliometric review analysis, we analyzed 143 peer-reviewed articles on NFT in cognitive impairment between 2001 and 2022 to track the research progress in this specific area. The Scopus database was searched using "neurofeedback in cognitive impairment" as the main theme for the bibliometric analysis. In this analysis, bibliometric data of co-occurrence, citations, author keywords, and publications were briefly discussed. Neuroimage was the most cited source, with 27% of the total citations. The United States was the major country contributor, with 27.83% of the pieces of literature, and it also became the major top co-authorship country with 28% of citations, making it the most active country in the study of neurofeedback in CI. Malaysia was listed as one of the top 20 countries in terms of top co-authorship and top 14 in terms of high citations. The theme of the top search keywords by authors was related to the NFT techniques, while the least searched theme was related to the synonyms of NFT. The present study integrated bibliometric data on the current status and future directions of NFT research in the context of CI. These findings could benefit researchers in planning future studies that could help in the realization of NFT as a potential clinical neurorehabilitation intervention in a wide range of clinical settings. In conclusion, our study offers a perspective of the progress of NFT research and identifies the most significant interests in this field.